Public service broadcasting - McQuail, Denis (Javnost (Ljubljana), 2003)
As public broadcasting in Europe has declined in relative terms in the overallsupply of television broadcasting, its activities have become more subject to scrutiny, both by regulatory authorities and by its competitors. The result is a threat of greater control and less genuine independence. In some countries, the price exacted for continuing financial support is increased accountability according to more narrowly defined criteria of performance. The central argument of this article is that public broadcasting should in principle enjoy the same freedom to publish as other media, within the limits of its special legal and constitutional position. Further, freedom should not be an obstacle to meeting social responsibilities and may even contribute to this goal. This view is supported by a closer look at the natureof media accountability, which has to be clearly differentiated from regulation and control.
Keywords: mass media; množični mediji; radio; television; televizija; democracy; demokracija; država; state; vplivi